Cyclic loading tests of thin-walled square steel tube beam-column joint with different joint details. (June 2020) - Bian, Jinliang; Cao, Wanlin; Zhang, Zongmin; Qiao, Qiyun
Abstract: To study the seismic performance of a thin-walled square steel tube beam-column joint of a light steel frame, 8 kinds of thin-walled square-hollow structural steel (HSS) and concrete-filled steel tube (CFST) beam-column joints with different joint details were designed and manufactured. The joint details were divided mainly into welded joint, plate joint, angle joint and angle with stiffener joint. A total of 14 specimens of beam-column joint specimens were tested using a low reversed cyclic loading test. The failure characteristic, load-bearing capacity, hysteretic property, stiffness degradation and energy dissipation were compared. The results showed that the different joint details had a great influence on the seismic performance of the beam-column joint. The bearing capacity and failure rotation of the welded joint were poor. The bearing capacity of the plate joint was close to that of the welded joint, but it showed improved bearing capacity, failure rotation and energy dissipation capacity of the joint. The bearing capacity of the angle joint was poor. With the angle welded stiffener, the bearing capacity, stiffness and energy dissipation capacity of the joints were significantly improved. The number and height of the stiffener can improve the seismic performance of the joint. The stiffness and energy dissipation capacity of the CFST beam-column joint was better than that of the HSS beam-column joint with the same joint detail. The classification of the joint is discussed, and a simplified M-R calculation model is proposed.